Quality of life outcomes following pediatric lung transplantation. Issue 11 (14th September 2017) - Lazor, Tanya; Grasemann, Hartmut; Solomon, Melinda; Anthony, Samantha J.
Abstract: Purpose: Compared to other solid organs, survival after lung transplantation (LTx) is still poor. Discussions on survival benefits following LTx in children, however, have largely concentrated on medical outcome data. Little research describes quality of life (QoL) of pediatric LTx recipients, which is partly due to the small number of pediatric LTxs performed. Only two centers worldwide performed >10 pediatric LTxs in 2013, making data on QoL in this population difficult to obtain. The primary objective was to examine the impact of LTx on QoL of pediatric recipients. Methods: LTx recipients aged 8‐17 years and their parents were recruited from a Canadian pediatric transplant centre. Participants completed the PedsQL 4.0 Generic Core Scales, a validated health‐related QoL patient‐reported outcome measure for children and adolescents, pre‐transplant and two times post‐transplant. Pre‐LTx QoL scores were compared with initial assessment scores post‐LTx and changes in QoL over time were described. Correlations between self‐ and proxy‐reports were also discussed. Results: Ten pediatric LTx recipients (six male, mean age = 13.3 years) and their parents were enrolled. Assessments were completed pre‐LTx (mean months = 4.8) and two times post‐LTx (mean months 8.7 and 24.6, respectively). Pre‐ and post‐transplant total scores differed significantly for both self‐ and proxy‐report, which remained consistent at a second assessment post‐transplant ( P  = 0.018 and 0.028, respectively). Conclusions: Findings highlight the importance of QoL outcomes when exploring LTx as a treatment option. Future research should explore long‐term QoL outcomes post‐LTx and examine standardized integration of patient‐reported outcomes into clinical practice.